2021
DOI: 10.1002/batt.202100029
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Electrolyte Development and Design Strategies for Next‐Generation Potassium‐Ion Batteries

Abstract: Rechargeable lithium‐ion batteries (LIBs) have attained tremendous success and are extensively used in a wide range of fields. However, due to the scarcity and uneven geographical distribution of Li resources, its price is steadily increasing, which may limit its sustainable application in the near future. Potassium‐ion batteries (PIBs) are promising alternatives to LIBs owing to the earth abundance, low cost, and eco‐friendliness of potassium, and high energy density of PIBs. Although the field of PIBs has se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 140 publications
1
16
0
Order By: Relevance
“…Overall, the ionic conductivity of the SAn sample compares well with those typically found in the literature for GPEs used in KIBs and appears to be amongst the highest encountered in the field for biobased quasi-solid polymer electrolytes. 49 Indeed, the cardanol-based electrolyte ionic conductivity at room temperature (10 –3 S cm –1 ) exceeds by one order of magnitude the values usually obtained for relevant quasi solid-state electrolytes previously published in the literature. This is valid also for the well-established PEO-based matrices.…”
Section: Resultsmentioning
confidence: 78%
“…Overall, the ionic conductivity of the SAn sample compares well with those typically found in the literature for GPEs used in KIBs and appears to be amongst the highest encountered in the field for biobased quasi-solid polymer electrolytes. 49 Indeed, the cardanol-based electrolyte ionic conductivity at room temperature (10 –3 S cm –1 ) exceeds by one order of magnitude the values usually obtained for relevant quasi solid-state electrolytes previously published in the literature. This is valid also for the well-established PEO-based matrices.…”
Section: Resultsmentioning
confidence: 78%
“…Using high concentrations of KFSI-DME, ~99.3% of coulombic efficiency and charge preservation above 80% were achieved beyond 99 cycles. The authors reported that a high concentration of DME-KFSI enabled the restriction of the oxidation reaction, leading to corrosion and dendrite formation [446]. This restriction occurs because DME and K + ions are closely bonded in a highly concentrated electrolyte solution, where the HOMO level will be reduced, mitigating oxidative decomposition reactions.…”
Section: K-based Batteriesmentioning
confidence: 99%
“…The current growth in the exploitation of renewable energy sources increases the need for efficient energy storage systems, in particular electrochemical devices such as batteries [1–5] . At present, lithium‐ion batteries (LIBs), working through the rocking chair mechanism, dominate the market of electrochemical energy storage devices, owing to their superior energy/weight ratio, long cycle life and fast charge‐discharge processes [6–10] .…”
Section: Introductionmentioning
confidence: 99%